2019
DOI: 10.1111/desc.12822
|View full text |Cite
|
Sign up to set email alerts
|

Early adversity in rural India impacts the brain networks underlying visual working memory

Abstract: There is a growing need to understand the global impact of poverty on early brain and behavioural development, particularly with regard to key cognitive processes that emerge in early development. Although the impact of adversity on brain development can trap children in an intergenerational cycle of poverty, the massive potential for brain plasticity is also a source of hope: reliable, accessible, culturally agnostic methods to assess early brain development in low resource settings might be used to measure t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
67
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 54 publications
2
67
0
Order By: Relevance
“…Another study used a portable fNIRS system to investigate the neural networks underlying VWM processing in infants and children in rural India. They found that VWM performance was inversely correlated with activation in the bilateral frontal cortices, such that increased activation in this area was associated with poorer VWM performance (Wijeakumar et al, 2019). This study highlights another crucial advantage of fNIRS over other neuroimaging modalities -its portability, allowing researchers to freely explore cognitive processes outside of a traditional lab setting.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Another study used a portable fNIRS system to investigate the neural networks underlying VWM processing in infants and children in rural India. They found that VWM performance was inversely correlated with activation in the bilateral frontal cortices, such that increased activation in this area was associated with poorer VWM performance (Wijeakumar et al, 2019). This study highlights another crucial advantage of fNIRS over other neuroimaging modalities -its portability, allowing researchers to freely explore cognitive processes outside of a traditional lab setting.…”
Section: Introductionmentioning
confidence: 74%
“…However, this limitation is less pronounced in children due to their smaller brains and thinner skulls (Buss et al, 2014). fNIRS has also been reliably used across the lifespan to study changes in activation in the frontal and parietal networks underlying VWM (Buss et al, 2014;Sato et al, 2013;Wijeakumar et al, 2019Wijeakumar et al, , 2017aWijeakumar et al, , 2017b. HOME ASSESSMENT OF VISUAL WORKING MEMORY Using fNIRS, Tsujimoto and colleagues (2004) examined VWM performance on a CD task in a sample of adults and five-year-old children.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, correlations between these responses and psychosocial risks, such as maternal education, maternal stress and the caregiving environment, are also reported. Wijeakumar et al report findings from a Globalfnirs study investigating early adversity in rural India, focusing on the impact on the functional brain networks underlying visual working memory [41]. Forty-two 4-to 48-month-olds were recruited from the most populous region in India, Uttar Pradesh, where children are exposed to poverty-related developmental challenges from early infancy, and thus represent a population relatively similar to that of the above-mentioned study.…”
Section: Current Studies Implementing Fnirs In Low-and Middle-income mentioning
confidence: 99%
“…Numerous studies included in this issue present adaptation and/ or testing of behavioral and neuroimaging measures to ensure that these are locally appropriate, feasible, and acceptable for measurement of children's behavioral (Milosavljevic et al, ; Obradović et al, ; Willoughby, Piper, Oyanga, & Merseth, ), language (Dulay, Cheung, & McBride, ; Jasińska, Wolf, Jukes, & Dubeck, ; Knauer, Kariger, Jakiela, Ozier, & Fernald, ; Lervåg, Dolean, Tincas, & Melby‐Lervåg, ), and neural development (Lloyd‐Fox et al, ; Perdue et al, ; Pyykkö et al, ; Turesky et al, ; Wijeakumar, Kumar, M. Delgado Reyes, Tiwari, & Spencer, ). Milosavljevic et al (), for example, test the adaptation of the Mullen Scales of Early Learning in the Gambia and cast light on developmental patterns in children aged 5–24 months.…”
Section: Introduction To Special Issue On Global Child Development Stmentioning
confidence: 99%
“…mentPerdue et al, 2019;Pyykkö et al, 2018;Turesky et al, 2019;Wijeakumar, Kumar, M. Delgado Reyes, Tiwari, & Spencer, 2019) Milosavljevic et al (2019),. for example, test the adaptation of the Mullen Scales of Early Learning in the Gambia and cast light on developmental patterns in children aged 5-24 months.They identify a pattern of older children receiving lower scores and suggest that this may reveal a developmental period during which infants at risk for cognitive delay begin to exhibit early behavioral manifestations of exposure to adversity (e.g., poverty and malnu-trition).…”
mentioning
confidence: 99%